Figuring the past : period film and the mannerist aesthetic (2012)
In the introduction to his evocatively titled book The Past is a Foreign Country, David Lowenthal remarks that ‘it is no longer the presence of the past that speaks to us, but its pastness’. This subtle distinction underlies the pleasures of the period film, in which the ‘the Past’ (as original myth or foundational mo- ment) resonates in the present through the visual (and aural) spectacle of past- ness, and its intricate signs. The period film stages a return to a place and time whose codes may seem strange and, more often than not, irrelevant. However, period objects and rituals are a source of continuing fascination, which accounts for the genre’s enduring popularity. Behind the apparent nostalgia for the es- sence of something lost, there is always something found that becomes mean- ingful for each generation of viewers, inscribed in the ways we imagine the past according to the needs and expectations of the present. This book explores the period film by focusing on the visual pre-eminence given to its figures of mean- ing. The notion of figure provides a prism through which to look at a film genre that thrives on convention and variation. Focusing on a cycle of films made between and , I will be discussing the ways these films project the contemporary historical imagination through a unique aesthetic that engages with the textures of the past in distinctive ways.